Pré-textuais: Cadernos Macambira: Anais do I Congresso de Educação do IF Baiano, Campus Guanambi (Cadernos Macambira, 2024)
Pré-textuais: Cadernos Macambira: Anais do I Congresso de Educação do IF Baiano, Campus Guanambi